2001
DOI: 10.1182/blood.v98.10.3162
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of peripheral blood OX40+(CD134+) T cells with chronic graft-versus-host disease in patients who underwent allogeneic hematopoietic stem cell transplantation

Abstract: There is no reliable laboratory indicator of the onset of chronic graft-versus-host disease (cGVHD). This study looks at whether the expression of OX40, a member of the tumor necrosis factor receptor family, is related to the development of cGVHD in patients who underwent allogeneic hematopoietic stem cell transplantation. Peripheral blood mononuclear cells from 22 patients after day 100 were subjected to multicolor flow cytometry. The percentages of both OX40 ؉ CD4 ؉ and OX40 ؉ CD8 ؉ T cells were significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
27
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 18 publications
2
27
0
Order By: Relevance
“…ϩ and CD4 ϩ T cells in SLE (43) and in chronic graftvs-host disease (44). The expression of CD134 may directly contribute to activation of type 2 cells.…”
Section: Cd45rcmentioning
confidence: 99%
“…ϩ and CD4 ϩ T cells in SLE (43) and in chronic graftvs-host disease (44). The expression of CD134 may directly contribute to activation of type 2 cells.…”
Section: Cd45rcmentioning
confidence: 99%
“…Modulation of the OX40-OX40L pathway potently ameliorates autoimmune-like diseases, such as experimental autoimmune encephalomyelitis (12), graft-versus-host disease (13), asthma (10), and arthritis (14). We have previously linked increased levels of cholesterol to upregulation of OX40 expression on T cells and showed that interruption of the OX40-OX40L interaction using an OX40L-blocking Ab leads to a reduction in the initiation of atherosclerosis (15).…”
mentioning
confidence: 99%
“…31,58,59 In humans, OX-40 (CD134, a member of TNF receptor superfamily responsible for costimulation) expressing CD4 ϩ cells are reportedly associated with onset of chronic GVHD and decreased response to initial therapy. 60 If OX-40 is a marker of cells involved in chronic GVHD, then targeting these cells or their interactions at the onset of chronic GVHD may be therapeutic. In mice, antibody to the OX-40 ligand (OX-40L) decreases acute GVHD, but to this point, human trials have not been conducted.…”
mentioning
confidence: 99%